2006
DOI: 10.1071/ar05111
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb bone growth and mineral maturation as potential indices of skeletal maturity in sheep

Abstract: The aim of this study was to characterise the allometric growth and bone mineral maturation of forelimb bones in sheep throughout the growth phase. Forelimb bones (scapula to proximal phalanx) were measured in 84 Merino sheep from similar genetic stock of approximately 12, 32, 64, 84, 116, and 168 weeks of age, with approximately equal numbers of wethers and ewes in each age cohort (n = 14). Sheep were selected for divergence of size, body weight, and condition, in order that the effects of age and body size c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Allometric analysis of length v. total limb bone length (Table 2) confirmed that, as shown previously (Cake et al 2006b), most limb bones obey a strict allometric relationship with the greater limb length, though this relationship is less consistent (i.e. higher residual error and lower r 2 values) for the fore and hind cannon bones.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Allometric analysis of length v. total limb bone length (Table 2) confirmed that, as shown previously (Cake et al 2006b), most limb bones obey a strict allometric relationship with the greater limb length, though this relationship is less consistent (i.e. higher residual error and lower r 2 values) for the fore and hind cannon bones.…”
Section: Resultssupporting
confidence: 82%
“…This is only partly consistent with tooth eruption data from the same study (Hopkins et al 2007), showing that BL × M and PD g × BLM, but not PD m × M, lambs showed earlier eruption of permanent dentition. In agreement with this discrepancy, bone magnesium content of PD m × M lambs at earlier timepoints was also consistent with the mineral profile of physiologically less mature animals, despite their more relatively advanced skeletal maturity (Ravaglioli et al 1996;Cake et al 2006b). Similarly, although ewes are known to mature earlier in terms of metacarpal growth plate closure (Ho et al 1989;Jeremiah et al 1997) and were clearly demonstrated in this study to be earlier maturing skeletally, the absence of a gender difference in bone magnesium content and the later eruption of permanent dentition in ewes shown by Hopkins et al (2007) suggests this does not necessarily reflect earlier physiological maturation.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations